The Effect of Extended Unemployment Benefit on the Job Finding Hazards: A Quasi-Experiment in Japan - Tomohiro Machikita; Miki Kohara; Masaru Sasaki (Institute for the Study of Labor (IZA), 2013)
This paper studies how changes in extended unemployment insurance (UI) benefit affect the duration of unemployment. We investigate this question by exploiting not only strict age thresholds but also the pre-displacement tenure and the reason for separation from the previous job in the Japanese UI system which determines a worker's maximum potential UI benefit duration at the age of 45. Job-seekers who became unemployed due to exogenous reasons (such as establishment closure) at the age threshold of 45 who have longer pre-displacement tenure receive maximum benefits for longer durations. This rule creates a local randomized experiment. Using a large administrative dataset to implement a difference-in-differences approach for the narrow age range of 44-46 who entered unemployment in the same month in the same year, we find that longer maximum benefit durations do not lead to a decrease in the jobless hazard; the duration of unemployment is not prolonged among jobseekers who have longer maximum benefit duration. This result is robust to shorter and longer tenure before entering unemployment. The non-negative effect on the jobless hazard is primarily due to a small difference in maximum duration between the treated group and the control group. In addition, workers with firm-specificity are likely to take any job in difficult position. Since the disincentive effects of UI benefit is weaker among UI recipients with firm-specific human capital, the results suggest that extending UI benefit of prime-age job-seekers with longer tenure at previous job is an effective tool to enhance welfare.
Keywords: J64; J65; J68; 330; maximum benefit durations; unemployment hazard; administrative data